Public Trust Doctrine: Constitutional Safeguards and Judicial Interpretations towards Healthy Agriculture - Deshani Thabrew, K.C. (University of Jaffna, 2016)
Effectiveness of modern agriculture and rapid environmental degradation is a matter that has to be addressed when dealing with the topic of environmental protection under the area of law and agriculture. Constitution of Sri Lanka provides few mechanisms to protect environment and Public Trust Doctrine (PTD) can be utilized as a remedial opportunity for challenges arising from modern agriculture. Combination of Article 3 and Article 4 of the 1978 constitution creates PTD in Sri Lanka. The doctrine states that the government is deemed to be the trustee of the natural resources of the country which must be held in the interest of people as beneficiaries. It is widely interpreted as the present generation holds the natural resources in trust for the future generations. In establishing the PTD, major lacunas can be identified in Sri Lankan legal system such as; doctrine is only recognized partially by the constitution as an entrenched provision, doctrine is vague as no specific criterions designed for its applicability, judiciary has no specific jurisdiction to deal with the matters connected with the doctrine other than the fundamental rights jurisdiction and no specific mechanism is available to people to commence litigations where the PTD is violated. The study discusses the information collected from law books, journals and articles written by public law experts to study how the application of the doctrine has to be adopted according to Sri Lankan legal framework and to overcome legal issues arising when implement the PTD. It is recommended that to adopt a people closer constitutional mechanism to safeguard the PTD as it automatically encourages the judicial activism in the country as the guardian of sovereignty in Sri Lanka
Keywords: Constitution; Entrenched Provision; Fundamental rights jurisdiction; Judicial activism; Sovereignty